Shadow of the solstice [compact disc, unabridged] - Hillerman, Anne, 1949- (Hillerman, Tony. Leaphorn and Chee novel., 2025)
The Navajo Nation police are on high alert when a U.S. Cabinet Secretary schedules an unprecedented trip to the little Navajo town of Shiprock, New Mexico. The visit coincides with a plan to resume uranium mining along the Navajo Nation border. Tensions around the official's arrival escalate when the body of a stranger is found in an area restricted for the disposal of radioactive uranium waste. Is it coincidence that a cult with a propensity for violence arrives at a private camp group outside Shiprock the same week to celebrate the summer solstice? When the outsiders' erratic behavior makes their Navajo hosts uneasy, Officer Bernadette Manuelito is assigned to monitor the situation. She finds a young boy at grave risk, abused women, and other shocking discoveries that plunge her and Lt. Jim Chee into a volatile and deadly situation. Meanwhile, Darleen Manuelito, Bernie's high spirited younger sister, learns one of her home health clients is gone-and the woman's daughter doesn't seem to care. Darleen's curiosity and sense of duty combine to lead her to discover that the client's grandson is also missing and that the two have become ensnared in a wickedly complex scheme exploiting indigenous people. Darleen's information meshes with a case Chee has begun to solve that deals with the evil underside of human nature.